1997
DOI: 10.1080/01635589709514603
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lycopene decreases the initiation of liver preneoplastic foci by diethylnitrosamine in the rat

Abstract: To test whether carotenoids can modulate the initiation of liver preneoplasia by diethylnitrosamine (DEN) or by 2-nitropropane (2-NP) in a sequential protocol of hepatocarcinogenesis, male weanling rats were fed for three or four weeks (respectively) diets containing beta-carotene, canthaxanthin, astaxanthin, or lycopene (300 mg/kg diet) or an excess of vitamin A (15,000 retinol equivalents/kg diet) or were treated intraperitoneally with 3-methylcholanthrene. During this period, all rats were injected intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 48 publications
2
60
1
1
Order By: Relevance
“…Astorg et al [153,154] demonstrated in two studies that β-carotene failed to exhibit any chemopreventive activity against a variety of chemically-induced hepatocarcinogenesis models in rats. This includes absence of effects on the number and size of preneoplastic foci in male Wistar rats that were induced with DENA/2-AAF, DENA or 2-nitropropane (2-NP) to develop preneoplastic liver foci.…”
Section: Rj Et Al Terpenoids and Liver Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…Astorg et al [153,154] demonstrated in two studies that β-carotene failed to exhibit any chemopreventive activity against a variety of chemically-induced hepatocarcinogenesis models in rats. This includes absence of effects on the number and size of preneoplastic foci in male Wistar rats that were induced with DENA/2-AAF, DENA or 2-nitropropane (2-NP) to develop preneoplastic liver foci.…”
Section: Rj Et Al Terpenoids and Liver Cancermentioning
confidence: 99%
“…However, only two studies were successful in achieving any beneficial effects exerted by these carotenoids. Astorg et al [153,154] conducted two studies with canthaxanthin and astaxanthin, and did not observe any preventive effects exerted by them against chemically-induced hepatocarcinogenesis in male Wistar rats. A dietary treatment regimen of either carotenoid at 300 mg/kg for 3 wk did not modify the number and size of GGT or GSTp foci in rats subjected to DENA or 2-NP hepatocarcinogenic regimen.…”
Section: Rj Et Al Terpenoids and Liver Cancermentioning
confidence: 99%
See 3 more Smart Citations